a/ 2x3 (2xy + 6x5y) b/ 3 1 x 5y 3 ( 4xy2 + 3x + 1) c/ 4 1 x 3yz (-2x2y 4 – 5xy) d/ (2x3 + 5y2 )(4xy3 + 1) e/ (5x – 2y)(x2 – xy + 1) f/ (x – 1)(x + 1)(x + 2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
2)
\(A=2x^2+2x+y^2-2xy=x^2-2xy+y^2+x^2+2x+1-1\)
\(=\left(x-y\right)^2+\left(x+1\right)^2-1\ge-1\)
Dấu \(=\)khi \(\hept{\begin{cases}x-y=0\\x+1=0\end{cases}}\Leftrightarrow x=y=-1\).
Vậy GTNN của \(A\)là \(-1\)đạt tại \(x=y=-1\).
\(B=2a^2+b^2+c^2-ab+ac+bc\)
\(2B=4a^2+2b^2+2c^2-2ab+2ac+2bc\)
\(=a^2-2ab+b^2+a^2+2ac+c^2+b^2+2bc+c^2+2a^2\)
\(=\left(a-b\right)^2+\left(a+c\right)^2+\left(b+c\right)^2+2a^2\ge0\)
Dấu \(=\)khi \(a=b=c=0\).
Vậy GTNN của \(B\)là \(0\)đạt tại \(a=b=c=0\).
1.
a) \(2x^2+2x+1=x^2+x^2+2x+1=x^2+\left(x+1\right)^2=0\)
\(\Leftrightarrow\hept{\begin{cases}x=0\\x+1=0\end{cases}}\)(vô nghiệm)
suy ra đpcm
b) \(x^2+y^2+2xy+2y+2x+2=\left(x+y\right)^2+2\left(x+y\right)+1+1=\left(x+y+1\right)^2+1>0\)
c) \(3x^2-2x+1+y^2-2xy+1=x^2-2xy+y^2+x^2-2x+1+x^2+1\)
\(=\left(x-y\right)^2+\left(x-1\right)^2+x^2+1>0\)
d) \(3x^2+y^2+10x-2xy+26=x^2-2xy+y^2+x^2+10x+25+x^2+1\)
\(=\left(x-y\right)^2+\left(x+5\right)^2+x^2+1>0\)